PELATIHAN OPERATOR KOMPUTER UNTUK MENINGKATKAN KOMPETENSI PEMUDA DI LUWU - Suluh, Sallolo; Bethony, Frans Robert; Arhing, Fatmawati; Ridwan, Andika; Porayow, Tomy (LPPM Universitas Bina Bangsa, 2025)
Competency-based training programs are one of the solutions to overcome the Employment problems that we are currently facing at various levels of education throughout the country, this can be seen that job opportunities are often available but cannot be fulfilled due to the limited workforce who have the required skills. One way to overcome the employment problems we are facing is to carry out workforce skills training activities that are tailored to the needs of the competency-based labor market with the assumption that if they cannot fill the available job vacancies, prospective workers who have been trained can automatically open up jobs in the informal sector. The method implemented in this training is to open advertisements in the form of banners for Luwu youth who want to take part in computer operator training to register online. After the training participants have met the desired requirements, training is carried out which is trained directly by UKI Toraja Mechanical Engineering students who are carrying out the 2022 Professional KKN and are also employees who work at the Luwu Regency BLK. The results achieved in this community service activity are the Computer Operator Assistant Vocational Work Skills Implementation activity carried out at the UPT.BLK Luwu Regency Office from July 4 to August 18, 2022 with a total of 260 training hours and a training implementation time of 33 training days with 16 participants. All were declared successful and were entitled to receive a work training certificate.